Pandangan Alkitab tentang Gereja Sebagai Komunitas Pembelajaran dan Pembinaan Pada Masa Kini (Jurnal Pendidikan Agama dan Teologi, 2025)
Social changes due to technological advancements have transformed the way people relate and associate with one another. Relationships can now be developed more easily, more affordably, and more quickly. As a community, the church is "forced" to re-evaluate whether the methods of learning and faith formation that have been applied so far still meet the needs of today’s congregation. Using a qualitative method with a literature-based approach, the researcher investigates the biblical perspective on this issue and finds that close relationships among members are a key indicator in learning and faith formation, as exemplified by the early church. Bringing the church back to its original design as the family of God (oikos), while utilizing current technological advancements, will make the church a constructive place for learning and nurturing the faith of its members.